Citizens in the green transition: perceptions of urban forestry and biomass use, and strategies for a sustainable future - D'Adamo, Idiano; Gastaldi, Massimo; Iannilli, Martina; Manzotti, Giorgia (Frontiers in Sustainability, 2025)
Urban forestry is recognized as a strategic lever for addressing the environmental and social challenges of cities, improving quality of life and promoting sustainable regeneration processes. This paper aims to investigate how urban forestry and the use of wood biomass are perceived by citizens, assessing their role in terms of collective wellbeing, environmental sustainability and territorial regeneration, with particular attention to differences related to gender, age, and value orientations. The research is conducted through an online survey carried out in Italy, aimed at gathering the opinions and perceptions of the population on the subject. The results show broad consensus, with generally very positive assessments, but with interesting differences: women and young people are more sensitive to behavioral aspects and more willing to financially support forestry initiatives, while men and older people favor structural and collective benefits. The analysis also identified two main profiles: a pragmatic cluster, oriented toward tangible and immediate interventions, and a value-based cluster, more attentive to widespread benefits and everyday sustainability practices. The findings highlight the need for differentiated communication and governance strategies. Interventions targeting more pragmatic citizen groups should prioritize communicating tangible local benefits, such as visible improvements in urban quality, environmental mitigation and direct improvements in everyday life. Conversely, strategies targeting value-oriented groups should emphasize collective responsibility, long-term environmental stewardship, and the integration of sustainable practices into daily routines, ensuring that policy narratives are aligned with citizens' normative commitments. Overall, the study provides actionable and context-sensitive insights for designing participatory frameworks that can strengthen institutional trust and promote a just, inclusive, circular, and effective green transition.